Lomi Lomi massage for clearing interface fluid in Descemet stripping automated endothelial keratoplasty - Neiwete Lomi; Deepsekhar Das; M Vanathi; Noopur Gupta; Bhavna Chawla; Radhika Tandon (Indian Journal of Ophthalmology, 2025)
Background: Descemet stripping automated endothelial keratoplasty (DSAEK) is a popular posterior lamellar keratoplasty used to tackle corneal decompensation secondary to endothelial damage. The surgical procedure involves removing the corneal stroma, Descemet’s membrane along with the affected endothelium from the host, and then transplanting the same from the donor cornea.[1] During the surgery, fluid accumulation in between the DSAEK lenticule and the host corneal stroma is common occurrence. This interface fluid if not removed can lead improper positioning of the donor lenticule and in certain instances lenticule displacement. External corneal massage is a popular technique which is employed in order to evacuate this interface fluid.[2,3] Purpose: Lomi Lomi massage is a massage technique where the masseuse uses the back of both forearms alternately in a kneading fashion.[4] The authors describe a similar pattern of massage using 2 26G cannula in order to clear the interface fluid. Synopsis: The bimanual kneading movement acts by pressing the anterior lamella down, with the air bubble in the anterior chamber giving counter traction the lenticule from below. In the continuous Lomi Lomi movements, one instrument is kept pressed on the host anterior lamella which prevents the backflow of the fluid, whereas the advancement of the second instrument leads to squeezing of the remaining fluid out of the interface. Although certain instruments, namely, DSAEK roller, have been described for the evacuation of interface fluid, a long-term prospective study is required to compare effectiveness, ease of use, safety, clinical outcomes, and surgeon preference between it and Lomi Lomi massage technique to conclude which is better. Highlights: Lomi Lomi corneal massage can be used to clear interface fluid in DSAEK surgery. Video Link: https://youtu.be/cNhAxdgtQQI